Performance Analysis of Undifferenced NRTK Considering Time-Varying Characteristics of Atmosphere - Jun Li; Huizhong Zhu; Yangyang Lu; Mingze Zhang; Aigong Xu (Remote Sensing, 2023)
Network RTK (NRTK), one of the primary means of high-precision real-time kinematic positioning (RTK), has been widely used. The key to providing highly accurate positioning is the ambiguity of the reference station being correctly fixed, but the atmospheric errors must be handled carefully, which seriously affects the efficiency of ambiguity fixing. This paper aims to improve the efficiency of ambiguity fixing by studying the time-varying characteristics of atmospheric errors. Once reasonable constraints are imposed on atmospheric parameters in the uncombined observation model, it can better fix ambiguity. Atmospheric parameters are estimated by random walk at the reference station, and the power spectral density (PSD) of atmosphere is determined by real-time observations, instead of using empirical values or empirical models that do not consider atmospheric variations. The experimental results showed that the real-time estimated PSD can improve the ambiguity fixing time by 18.4% and the ambiguity fixing success rate for the reference station by 11.7%, compared with using empirical PSD for atmospheric parameters. Unlike general NRTK positioning based on differential error correction values, undifferenced NRTK estimates the integer ambiguity and undifferenced error correction value at a single reference station, ensuring the independence of the error correction value of each reference station, and it can be easily broadcast and received through the network, which is more convenient for realizing high-precision RTK positioning for users.